Interaction between Octenidine-based Solution and Sodium Hypochlorite: A Mass Spectroscopy, Proton Nuclear Magnetic Resonance, and Scanning Electron Microscopy–based Observational Study - Thaha, Khaleel Ahamed; Varma, R. Luxmi; Nair, Mali G.; Sam Joseph, V.G.; Krishnan, Unni (Journal of endodontics, 2017)
Octenisept (OCT; Schülke & Mayr, Nordersdedt, Germany), an antimicrobial, antibiofilm agent and a promising root canal irrigant, can be potentially combined with sodium hypochlorite (NaOCl) during endodontic treatment. The aim of this study was first to identify the precipitate formed on the interaction between OCT and NaOCl and secondly to compare its effect on dentinal tubules with that of precipitate formed on combining chlorhexidine (CHX) and NaOCl. This observational study was conducted in 3 stages. Initially, the color changes and precipitate formation were assessed when the test solution 0.1% OCT and 5.2% NaOCl were mixed. Color changes were compared with those observed when 2% CHX was mixed with 5.2% NaOCl. The residue obtained on combining OCT and NaOCl was subjected to proton nuclear magnetic resonance (1H NMR) and mass spectrometric (MS) analysis. In the final stage, dentinal surfaces irrigated alternatively with OCT and NaOCl were compared using scanning electron microscopy (SEM) with the dentinal surface irrigated with CHX and NaOCl. The OCT-NaOCl mixture changed in color from initial milky white to transparent over time, whereas the CHX-NaOCl mixture showed an immediate peach-brown discoloration. 1H NMR and MS analysis established that the whitish precipitate obtained on combining OCT and NaOCl solutions correlated with the structure of phenoxyethanol (PE). SEM revealed dense precipitate occluding the dentinal tubules with the CHX and NaOCl group, whereas the precipitate was sparse and partially occluded in the OCT and NaOCl group. The whitish precipitate formed with the OCT-NaOCl mixture was identified as PE, a compound already present in OCT, and it partly occluded the dentinal tubules. •When Octenisept (OCT) was added to NaOCl, the solution turned milky white and precipitated.•Mass spectroscopy and proton nuclear magnetic resonance analysis confirmed that the precipitate was phenoxyethanol.•Phenoxyethanol is inherently present in OCT.•The precipitate was sparsely distributed and only partly occluded the tubules.